Achieving heterogeneous structure in hcp Zr via electroplastic rolling - Li, Ming; Guo, Defeng; Li, Jingtao; Zhu, Shimin; Xu, Chao; Li, Kaifang; Zhao, Yadan; Wei, Bingning; Zhang, Qian; Zhang, Xiangyi (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2018)
Heterogeneous structure has been widely used to enhance the poor ductility of high-strength nanostructured materials. However, it is still a challenge to form heterogeneous structures in hard-deformed materials. Here, by using electroplastic rolling and subsequent low-temperature annealing, a heterogeneous structure was formed in the hard-deformed hcp Zr and exhibited a good combination of high strength and good ductility. Its formation can be attributed to the effective microstructure refinement and high deformation energy storage during the electroplastic deformation process. The present study is important for the design and fabrication of heterogeneous structured metals and alloys.